2013
DOI: 10.1016/j.cub.2013.09.008
|View full text |Cite
|
Sign up to set email alerts
|

The human amygdala drives reflexive orienting towards facial features

Abstract: The human amygdala is reliably activated by facial expressions [1], but the precise functional relevance of such activity change is not well understood, because most previous studies did not allow for separating effects of the emotional expression from the distribution of specific facial features and neglected corresponding attentional processes. Findings on rare patients with bilateral amygdala damage indicate that the amygdala might be involved in triggering shifts of overt attention towards specific facial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 10 publications
(15 reference statements)
5
62
0
Order By: Relevance
“…Behavioural research presenting face parts (e.g., Calder, Young, Keane, & Dean,2000) or using response classification techniques such as Bubbles (e.g., Blais, Roy, Fiset, Arguin, & Gosselin, 2012;Smith et al, 2005) has highlighted the importance of these so-called "diagnostic features" for the discrimination and categorization of these facial emotions. Eyetracking research also supports the idea that attention is drawn to these features early on, as revealed by spontaneous saccades towards the eyes of fearful faces or the mouth of happy faces presented for as short as 150ms (Gamer, Schmitz, Tittgemeyer, & Schilbach, 2013;Scheller, Büchel, & Gamer, 2012). the most useful diagnostic information for the discrimination of fearful facial expressions and the mouth for the discrimination of happy facial expressions, and that the N170 peaks when these diagnostic features are encoded (Schyns, Petro, & Smith,2007).…”
Section: Role Of Facial Features In the Processing Of Facial Expressionmentioning
confidence: 72%
“…Behavioural research presenting face parts (e.g., Calder, Young, Keane, & Dean,2000) or using response classification techniques such as Bubbles (e.g., Blais, Roy, Fiset, Arguin, & Gosselin, 2012;Smith et al, 2005) has highlighted the importance of these so-called "diagnostic features" for the discrimination and categorization of these facial emotions. Eyetracking research also supports the idea that attention is drawn to these features early on, as revealed by spontaneous saccades towards the eyes of fearful faces or the mouth of happy faces presented for as short as 150ms (Gamer, Schmitz, Tittgemeyer, & Schilbach, 2013;Scheller, Büchel, & Gamer, 2012). the most useful diagnostic information for the discrimination of fearful facial expressions and the mouth for the discrimination of happy facial expressions, and that the N170 peaks when these diagnostic features are encoded (Schyns, Petro, & Smith,2007).…”
Section: Role Of Facial Features In the Processing Of Facial Expressionmentioning
confidence: 72%
“…However, previous studies have not controlled gaze fixation on the features of facial emotional stimuli. This is important given recent reports of spontaneous saccades toward the eyes of fearful expressions even with stimuli presented for only 150ms (Gamer et al, 2013). We hypothesized that the early ERP modulations of the N170 by fearful faces previously reported might have been driven by attention to the eyes.…”
Section: Early and Later Lateral Posterior Effects For Fearful Expresmentioning
confidence: 90%
“…The eye region is used most prominently when discriminating fear from other expressions (Smith, Cottrell, Gosselin, & Schyns, 2005) and eyes have been shown to convey threat even when presented in isolation (Fox & Damjanovic, 2006;Whalen et al, 2004). Recently, it has been shown that participants make spontaneous saccades toward the eyes of emotional faces presented even for as short as 150 ms (Gamer, Schmitz, Tittgemeyer, & Schilbach, 2013). Given that previous ERP studies reporting modulations of the N170 with fearful faces did not use an eye-tracker to confirm gaze position, and that the eyes are salient in fearful faces, it is possible that the participants made small eye movements toward the eyes or attended the eyes more for fearful faces than other expressions.…”
Section: Introductionmentioning
confidence: 99%
“…In support of this, OT administration increases VTA activation during social stimuli processing (Groppe et al, 2013). Recent research underlines the crucial role of the amygdala in detection of socially salient facial features (Gamer et al, 2013). Current pathways suggest that IN-OT administered into the CNS via the olfactory bulb reaches the amygdala.…”
Section: Top-down Level Modulation Of Social Information Processingmentioning
confidence: 92%